Comparative Analysis of Mental Expenses for End-Level Students in Dealing with Online and Direct Learning with the NASA-TLX Method (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Limitation of direct physical interaction related to the Covid-19 pandemic has an impact on the education sector, where all learning activities are carried out online to limit physical interactions. Online learning methods are considered more flexible to do when compared to direct learning methods. This research was conducted to determine how much difference the mental load felt by final year students in online learning and direct learning. Measurement of a mental load was carried out using the National Aeronautics and Space Administration Task Load Index (NASA-TLX) method by distributing questionnaires containing six subscales of mental load measurement to final year students of four different study programs, including Management, Accounting, Informatics Engineering, and English. The six subscales used include Mental Demands, Physical Demands, Temporal Demands, Own Performance, Effort, and Frustration. Based on the results of the average calculation of the four sample groups, it shows that the mental load of online learning is 0.4% greater than direct learning, 81.3% and 80.9%, respectively.